Mechanistic insights into Nav1.7‐dependent regulation of rat prostate cancer cell invasiveness revealed by toxin probes and proteomic analysis. (5th April 2019) - Chen, Bo; Zhang, Changxin; Wang, Zijun; Chen, Yan; Xie, Huali; Li, Sha; Liu, Xiaoqian; Liu, Zhonghua; Chen, Ping
Abstract : Voltage‐gated sodium channels are involved in tumor metastasis, as potentiating or attenuating their activities affects the migration and invasion process of tumor cells. In the present study, we tested the effect of two peptide toxins, JZTX‐I and HNTX‐III which function as Nav1.7 activator and inhibitor, respectively, on the migration and invasion ability of prostate cancer (PCa) cell line Mat‐LyLu. These two peptides showed opposite effects, and subsequently a comparative proteomic analysis characterized 64 differentially expressed membrane proteins from the JZTX‐I‐ and HNTX‐III‐treated groups. Among these, 15 proteins were down‐regulated and 49 proteins were up‐regulated in the HNTX‐III group. Bioinformatic analysis showed eight proteins are cytoskeleton proteins or related regulators, which might play important roles in the metastasis of Mat‐LyLu cells. The altered expressions of four of these proteins, fascin, muskelin, annexin A2, and cofilin‐1, were validated by western blot analysis. Further function network analysis of these proteins revealed that the Rho family GTPases RhoA and Rac1 might be of particular importance for the rat PCa cell invasion. Pharmacological data revealed that JZTX‐I and HNTX‐III could modulate the Rho signaling pathway in a Nav1.7‐dependent manner. In summary, this study suggests that the Nav1.7‐dependent regulation of Rho GTPase activity plays a vital role in Mat‐LyLu cell migration and invasion and provides new insights into the treatment of PCa. Abstract : Prostate cancer (PCa) is a major cause of disease and mortality among men. In this paper, we found that the Nav1.7 modulators JZTX‐I and HNTX‐III have potential effects on the migration and invasion of Mat‐LyLu PCa cells. This study strengthens the functional link between Nav1.7 activity and tumor metastasis revealing new insights in PCa biology, and highlights the potential of developing metastasis modulators from Nav1.7 inhibitors or activators.